ANALISIS PENGARUH INFLASI DAN SUKU BUNGA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 2005 – 2015 - Siwi Nur Indriyani (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
The research studied to determine the effect of The Inflation, and Interest Rate to Indonesia’s Economic Growth In Indonesia’s The Period 2005 – 2015. The data that used in this research is secondary data namely The Inflation, and Interest Rate which devired from the website of bank Indonesia and Badan Pusat Statistik (BPS). The method used is multiple linear regression. The regression of research results show that simultaneoust the inflation and Interest Rate does significant effect to Indonesia’s economic growth in the year 2005 – 2015.